Efficacy of Gamma Knife Radiosurgery for Recurrent High-Grade Gliomas with Limited Tumor Volume - Cheon, Young-Jun (J Korean Neurosurg Soc, 2018)
OBJECTIVE: This study aims to determine whether gamma knife radiosurgery (GKR) improves survival in patients with recurrent highgrade gliomas. METHODS: Twenty nine patients with recurrent high-grade glioma underwent 38 GKR. The male-to-female ratio was 10 : 19, and the median age was 53.8 years (range, 20–75). GKR was performed in 11 cases of recurrent anaplastic oligodendrogliomas, five anaplastic astrocytomas, and 22 glioblastomas. The median prescription dose was 16 Gy (range, 10–24), and the median target volume was 7.0 mL (range, 1.1–15.7). Of the 29 patients, 13 (44.8%) received concurrent chemotherapy. We retrospectively analyzed the progression-free survival (PFS) and overall survival (OS) after GKR depending on the Eastern Cooperative Oncology Group (ECOG) performance status (PS), pathology, concurrent chemotherapy, radiation dose, and target tumor volume. RESULTS: Starting from when the patients underwent GKR, the median PFS and OS were 5.0 months (range, 1.1–28.1) and 13.0 months (range, 1.1–75.1), respectively. On univariate analysis, the median PFS was significantly long in patients with anaplastic oligodendroglioma, ECOG PS 1, and target tumor volume less than 10 mL (p<0.05). Meanwhile, on multivariate analysis, patients with ECOG PS 1 and target tumor volume less than 10 mL showed improved PFS (p=0.043 and p=0.007, respectively). The median OS was significantly increased in patients with ECOG PS 1 and tumor volume less than 10 mL on univariate and multivariate analyses (p<0.05). CONCLUSION: GKR could be an additional treatment option in recurrent high-grade glioma, particularly in patients with good PS and limited tumor volume.